The Guidelines for the management of solid waste, which case of Nakhon Pathom Municipality. - Nomnamsap, Dararat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This research aims to 1) to study the level of public participation in solid waste management in the area of Nakhon Pathom Municipality. 2) the study the effectiveness of solid waste management in the area of Nakhon Pathom Municipality. 3) to compare the personal factor and factors that contribute to the effectiveness of solid waste management in the area of Nakhon Pathom Municipality. 4) to study the guideline for the management of solid waste in the area of Nakhon Pathom Municipality, which sample is 400 people , derived by systematic random sampling, by using the descriptive statistical analysis, t-test, One Way ANOVA, including Interviews to analyze management practices. The research found that 1. The comments on the participation of citizens in the management of solid waste management as a whole were at a high level. 2. The comments on the effectiveness of solid waste management as a whole were at a high level. 3. The analysis to compare the differences of opinion on the effectiveness of solid waste management that classified by gender and income, both overall and in all aspects. The analysis found the difference is not statistically significant at the .05 analysis to compare the differences of opinion on the effectiveness by age, education and occupation. The overall and individual aspects Found that the difference was statistically significant at 0.05, 4. The Guidelines for the management of solid waste, which case of Nakhon Pathom Municipality; Nakhon Pathom Municipality should cooperate with the community in solid waste management. They should be starting to educate households, and announce the publicity campaign to identify the importance of separating waste. They should add more supply of equipment to provide adequate solid waste, and promote a system of solid waste disposal services. They should create awareness to the public about the problem of solid waste to adjust the attitude of the people about how importance of litter or solid waste disposal and the restrictions preliminary correctly. Article history : Accepted 25 November 2016 SIMILARITY INDEX = 3.10